DATABASE DENIALS. - Dudley, Melinda (Quill, 2007)
This article discusses how technology has revolutionized how information is created and stored and the impact that computers and databases have had on media access. Journalists have found that acquiring digital records has become an obstacle because of the format, not the content. Public officials and agencies have a variety of lawful reasons for denying digital public records, which parallel those for paper documents. Agencies are nor required to create a record if what is requested does not exist, nor are they obligated to reprogram data to meet the requester's needs.